2020
DOI: 10.1007/s11111-020-00364-4
|View full text |Cite
|
Sign up to set email alerts
|

Amenities or disamenities? Estimating the impacts of extreme heat and wildfire on domestic US migration

Abstract: For decades, Americans have generally been moving away from the Northeast and the Midwest toward the South and West. Mountainous and desert areas in the West and Southwest have been especially popular internal migration destinations. However, these same areas are particularly susceptible to the increasing impacts of climate change on extreme heat and wildfire. This paper investigates relationships between disasterlevel fire events and extreme heat on county-level migration in the USA using annual panel data fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 63 publications
2
15
0
3
Order By: Relevance
“…These findings contrast with prior research on non-wildfire rapid-onset environmental hazards, which has generally found that such events have little effect on migration. Our conclusions instead affirm previous research on a smaller subset of FEMA disaster-declared wildfire disasters, which has suggested that such fires are associated with heightened out-migration (Winkler and Rouleau, 2020).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…These findings contrast with prior research on non-wildfire rapid-onset environmental hazards, which has generally found that such events have little effect on migration. Our conclusions instead affirm previous research on a smaller subset of FEMA disaster-declared wildfire disasters, which has suggested that such fires are associated with heightened out-migration (Winkler and Rouleau, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…For fires ranging from 1 to 17 buildings de-stroyed, we instead observe relative immobility -no changes to in-migration or out-migration. This suggests that Winkler and Rouleau's hypothesized "disamenity shifts," wherein environmental characteristics previously considered by residents to be amenities instead come to be considered disamenities, are not occurring to any degree that has affected migration patterns among most residents living with wildfires (Winkler and Rouleau, 2020). This finding should temper any overstatements of mass migration away from fire-prone regions at present.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Additionally, panels of population-environment data can be constructed from administrative data. For example, also in this issue, Winkler and Rouleau (2021) put together a panel consisting of 25 years of observation on almost 3000 US counties from Census data on inand out-migration, NOAA data on extreme heat, Federal Emergency Management Agency (FEMA) data on wild-fire related disasters, US Department of Agriculture (USDA) data on amenities, Bureau of Economic Analysis (BEA) data on wages and salaries, and Bureau of Labor Statistics (BLS) data on unemployment. Clearly, data availability is not the limiting factor it once was.…”
Section: Where Things Stand Now: Key Accomplishmentsmentioning
confidence: 96%